Imperfection of tender document : a solution towards sustainable construction practice in Malaysia / Mohd Esham Mamat ... [et al.] - Mohd Esham, Mamat; Shahela, Mamter; Mohammad Sani, Mat Hussein; Norazlin, Mat Salleh (2015)
Nowadays, a tender document is the main duty of quantity surveyor during pre-contract stage of the project. It’s shall be well prepared toward a sustainable tendering and construction process. However, there are imperfections in tender document which will affect the flow in construction and to be a problem for the project. Tender document is important in the construction, especially to appoint a suitable renderer and it will be changed the contract document for the project. Imperfection in tender document also affects the parties involved in construction industry such as client, contractor, quantity surveyor and other parties to have discrepancies during the construction period. The aims of this study are to investigate the types, causes and implication of imperfection of tender document in our construction industry. In order to achieve the aim of this study, 100 numbers of questionnaires were distributed to the quantity surveyor who work in consultant firm and contractor firm. The data will be collect and analyse by using Statistical Package for the Social Sciences (SPSS) software. At the end of this study, expected findings regarding to this topic will be achieved and will come out with the recommendation and solution how to avoid or reduce the imperfection in tender document towards sustainable construction.